Structural Color Platforms: Multimodal and Covert–Overt Convertible Structural Coloration Transformed by Mechanical Stress (Adv. Mater. 25/2020). Issue 25 (24th June 2020) - Zhou, Qitao; Park, Jun Gyu; Bae, Juyeol; Ha, Dogyeong; Park, Jungyul; Song, Kyungjun; Kim, Taesung
Abstract : Self‐assembled SiO2 ‐nanoparticle patterns encapsulated by poly(dimethylsiloxane) are developed by Kyungjun Song, Taesung Kim, and co‐workers in article number 2001467 as a novel and simple color platform, which can switch between transparent and colored states by mechanical. Upon compression, wrinkles are generated as gratings, enabling the instant display and hiding of information, such as QR codes and trademarks, by external stimuli. The color platform could be applied in anticounterfeiting applications.